2019
DOI: 10.1021/acs.inorgchem.8b03489
|View full text |Cite
|
Sign up to set email alerts
|

C–O and C–N Functionalization of Cationic, NCN-Type Pincer Complexes of Trivalent Nickel: Mechanism, Selectivity, and Kinetic Isotope Effect

Abstract: This report presents the synthesis of new mono-and dicationic NCN-Ni III complexes and describes their reactivities with protic substrates. (NCN is the pincer-type ligand k N , k C , k N-2,6-(CH2NMe2)2-C6H3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We will also explore the potential reactivities of the cyclonickelated compounds described herein for oxidation-induced C–heteroatom functionalization reactions. These studies will draw inspiration from recently reported model systems based on NCN-type pincer-Ni III complexes that promote C–N, C–O, and C–halide bond formation reactions …”
Section: Discussionmentioning
confidence: 99%
“…We will also explore the potential reactivities of the cyclonickelated compounds described herein for oxidation-induced C–heteroatom functionalization reactions. These studies will draw inspiration from recently reported model systems based on NCN-type pincer-Ni III complexes that promote C–N, C–O, and C–halide bond formation reactions …”
Section: Discussionmentioning
confidence: 99%
“…Our long-standing interest in the synthesis and reactivities of high-valent Ni complexes , prompted us to use cyclic voltammetry (CV) to measure the one-electron oxidation potentials of the above-mentioned POC sp 3 N and POC sp 3 P complexes. The main objective of this exercise was to study the variations in redox potentials as a function of different structural features, and use any insight gleaned from such studies to prepare thermally stable high-valent derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Attempted oxidation of Ni(II)-TEMPOH complexes. Our long-standing interest in the synthesis and reactivities of high valent Ni complexes [56][57][58][59] prompted us to investigate the redox potential of the cyclometalated complexes under discussion. Cyclic voltammetry (CV) measurements of the η 1 -TEMPOH adducts prepared in the course of the study indicated that none supported reversible electrochemical oxidation: we observed in all cases essentially irreversible redox phenomena (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%